Observation of multiple rotons and multidirectional roton-like dispersion relations in acoustic metamaterials - Zhu, Zhenxiao (2023)
Roton dispersion relations were firstly predicted by Landau and have been extensively explored in correlated quantum systems at low temperatures. Recently, the roton-like dispersion relations were theoretically extended to classical acoustics, which, however, have remained elusive in reality. Here, we report the experimental observation of roton-like dispersions in acoustic metamaterials with beyond-nearest-neighbour interactions at ambient temperatures. The resulting metamaterial supports multiple coexisting modes with different wavevectors and group velocities at the same frequency and broadband backward waves, analogous to the ‘return flow’ termed by Feynman in the context of rotons. By increasing the order of long-range interaction, we observe multiple rotons on a single dispersion band, which have never appeared in Landau’s prediction or any other condensed-matter or classical-wave studies. Moreover, we have also theoretically proposed and experimentally observed multidirectional roton-like dispersion relations in a two-dimensional nonlocal acoustic metamaterial. The realization of roton-like dispersions in metamaterials could pave the way to explore novel physics and applications on quantum-inspired phenomena in classical systems.